2023
DOI: 10.3390/biology12030361
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Profiles of Chainsaw Hollows and Natural Hollows during Extreme Heat Events

Abstract: Loss of hollow-bearing trees threatens many hollow-dependent wildlife. To mitigate this process, artificial chainsaw-carved hollows (CHs) are often created in dead trees, yet little is known about their thermal profiles. We measured temperatures inside 13 natural hollows (8 live and 5 dead trees) and 45 CHs (5 live and 40 dead trees) in the central west of NSW, Australia, over the course of 2 summers. Maximum temperatures and daily temperature ranges within natural hollows and artificial hollows were similar i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…In the west-central of New South Wales, Australia, the temperatures inside 13 natural hollows and 45 artificial chainsaw-carved hollows (CHs) were measured over the course of two summers, and it was found that CHs created in dead trees might not provide suitable thermal conditions for hollow-dependent marsupials during summer heatwaves. Therefore, the authors concluded that the retention of large live trees and revegetation was crucial for conserving hollow-dependent fauna in natural and urban landscapes [12].…”
Section: Theme 1: Indicators and Services Of Urban Green Spacesmentioning
confidence: 99%
“…In the west-central of New South Wales, Australia, the temperatures inside 13 natural hollows and 45 artificial chainsaw-carved hollows (CHs) were measured over the course of two summers, and it was found that CHs created in dead trees might not provide suitable thermal conditions for hollow-dependent marsupials during summer heatwaves. Therefore, the authors concluded that the retention of large live trees and revegetation was crucial for conserving hollow-dependent fauna in natural and urban landscapes [12].…”
Section: Theme 1: Indicators and Services Of Urban Green Spacesmentioning
confidence: 99%
“…However, our results reveal that the historical silvicultural practice of ringbarking accounted for almost half of all dead trees. Dead hollow-bearing trees are a critical component of habitat provision (Thorn et al, 2020), but they have been shown to support four times fewer microhabitat types than living trees (Paillet et al, 2017) and their thermal properties differ from living trees which may limit their habitat suitability for some species (Griffiths et al, 2018;Callan et al, 2023). Further declines in hollow densities will occur in these forests due to the collapse of dead hollow-bearing trees (Lindenmayer et al, 2018).…”
Section: The Majority Of Large Trees Were Dead Suggesting Further Dec...mentioning
confidence: 99%